A Secure Dental Appointment System with One-Time Password Verification and Dual Authentication for Klinik Pergigian Sharifah - Azhar, Shahirah; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2023)
A web-based dental appointment system is the new standard method and most significant way to handle appointment scheduling difficulties. However, existing appointment booking at Klinik Pergigian Sharifah is done manually and is less organised, which may result in any missed scheduled appointment records. A Secure Dental Appointment System is proposed for the clinic in this study. The objective of this project is to develop and test a secure dental appointment system for Klinik Pergigian Sharifah. Additionally, One-Time Password verification using email for user registration and dual authentication using Knowledge-Based Authentication with a “Completely Automated Public Turing test to tell Computers and Humans Apart” (CAPTCHA) for user login is applied in the system. Basic security approaches including Role-Based Access Control, strong password validation and salt-hashing passwords are also implemented. This project uses an iterative waterfall model and includes all necessary phases. Based on system testing and user feedback, the system was effectively established, and project requirements are met. This project system might continuously improve its usability and efficiency with more features and security to offer a sufficient appointment system in the future.